Инвестициите и локалниот економски развој во тетовскиот регион - Мазлами, Јетон (Економски факултет, УКИМ, Скопје, 2011)
The national economy of the Republic of Macedonia is characterized with a still not suitable enough business environment, a low degree of internal and external investments, a high level of unemployment and poverty, all of this being followed by a low level of economic growth and development. Experience from the integrating processes of the developed national economies from the EU and the world, provide prove for the great importance of private and public investments, as well as the institutional and financial support for the real sector provided by the local and central government, in order to realize a higher degree of local, regional and overall economic development. In order to improve its macroeconomic indicators the Republic of Macedonia must adjust to the Euro integration process by implementing proper reforms and efficient economical politics in local and central levels of government. The preparation of this dissertation represents a responsible challenge for me, but at the same time a broader activity of great interest for the makers of the investment and development politics in local and central level in the Republic of Macedonia. The attractiveness and applications of this doctoral dissertation become even greater now days when the units of local governance in the Republic of Macedonia get a higher degree of autonomy and fiscal decentralization. The doctoral dissertation begins with an analysis of the most important theories of local and regional development and continues with the opportunities for the creation of a more suitable environment for investments, with the fostering of investments through institutional support that is the creation of business centres, technological parks, clusters, business incubators, business zones, investment funds, local agencies etc. The importance of local bonds as a contemporary approach for finding finance for investments is emphasized in the doctoral dissertation. Another issue that must be mentioned is the research of the contemporary forms of cooperation of the private sector with the public sector and the possibilities for their implementation in the municipalities in the Tetovo region. The main part of the doctoral dissertation is the empirical research of the experience of the Republic of Slovenia with special emphasis to the municipality of Maribor on one side and the Republic of Macedonia with special emphasis to the municipality of Tetovo on the other side. In this direction the questionnaire implemented in 200 business subjects in order to get a closer and better idea about investments, employment possibilities, the capacities and potential of the real sector in the Tetovo region should be mentioned. The Republic of Slovenia was one of the most successful Yugoslav Republics and at the same time the most efficient republic when it comes to the path chosen to join the EU, which makes it a suitable referent country-economy to draw positive experience for other republics, in this case The Republic of Macedonia. The economy of the Republic of Slovenia in general and the municipality of Maribor in particular compared to the municipality of Tetovo, has provided the necessary data for the creation of a model of economical development of the municipality of Tetovo and the Tetovo region of the Republic of Macedonia. The mission of the proposed model for the Tetovo region is oriented towards: higher investments in all economical branches and the developments of local economies, motivation and support of entrepreneurial ideas for higher investments (specially the Diaspora), the creation of an appropriate business climate, opportunities for new employments, creation of a proper living environment based on qualitative: education, culture, recreation and public administration. Finally, the proposed new development model for the municipality of Tetovo presents an argument to prove and accept the hypothesis of the dissertation.
Investments and Local Economic Development in the Tetovo Region
Докторска дисертација одбранета во 2011 година на Економскиот факултет во Скопје, под менторство на проф. д–р Методија Несторовски.
Keywords: investment (private/public), economic growth and economic development, gross domestic product (GDP), business subject (BS), business environment, employment, entrepreneurship, small business, local economic development (LED), private public partnership (PPP), units of local government (ULG), budget of ULG, revenues and expenditures, capital expenditures, public administration